Mild Upgrading of Bio‐Crude Pyrolysis Oil: A Concept Based on Bio‐Based Alcohols with Selective Water Adsorption. Issue 7 (6th December 2017) - Kumar Pazhavelikkakath Purushothaman, Rajeesh; Buntara, Teddy; Zhang, Zheng; Vehoff, Ilse J.; Boyadjian, Cassia; Falco, Lorena; Seshan, Kulathuiyer; Gómez, Natalia; Heeres, Hero J.; Melián‐Cabrera, Ignacio
Abstract: Biocrude pyrolysis oil is obtained by a process called fast‐pyrolysis, in which almost any organic‐based feedstock is thermally processed at moderate temperatures, in the range of 400–600 °C, in the absence of oxygen at short residence times. After condensing the vapors in a cooling tray, a dark‐brown bioliquid is obtained. The quality of the thus obtained fast pyrolysis oil has some barriers for its direct use as transportation fuel. Low caloric value, high viscosity, and corrosion are the major challenges for its implementation in conventional engines. There have been sustained efforts to improve the quality of the oil. In this Communication we are reporting a concept on improving the acidic properties by means of a combined catalysis and adsorption approach. We found that fast pyrolysis oil can be upgraded through alcoholysis using n ‐butanol and tetrahydrofurfuryl alcohol, which are biomass‐derived bulk chemicals. The reaction is acid catalyzed whereas water is continuously separated from the condensate mixture through molecular sieve adsorption. Under optimal conditions, the ultimate acidity and water content of the upgraded product are negligible. Abstract : Upgrading of pyrolysis oil : Fast pyrolysis oil can be optimally upgraded through alcoholysis using tetrahydrofurfuryl alcohol, a biomass‐derived bulk chemical. Water is continuously separated from the condensate mixture using a molecular sieve. The final acidity and water content of the optimal upgraded biocrude oil are negligible under the applied reaction conditions.